Building future scenarios and uncovering persisting challenges of participatory forest management in Chilimo Forest, Central Ethiopia - Kassa, H.; Campbell, Bruce M.; Sandewall, M.; Kebede, M.; Tesfaye, Y.; Dessie, G; Seifu, A.; Tadesse, M.; Garedew, E.; Sandewall, K. (2009)
We examined the changes in forest status and people’s livelihoods through building future scenarios for Chilimo Forest in Central Ethiopia where participatory forest management (PFM) is being implemented. Participatory methods were employed to collect data, and a dynamic modeling technique was applied to explore trends over time. By integrating the more quantitative model outputs with qualitative insights, information on forests and livelihoods was summarized and returned to users, both to inform them and get feedback. A scenario of open access without PFM provides higher income benefits in the short term but not over the longer term, as compared to a scenario with PFM. Follow up meetings were organized with national decision makers to explore the possibility of new provisions in the national forest proclamation related to joint community–state ownership of forests. Project implementers must constantly work towards improving short term incentives from PFM, as these may be insufficient to garner support for PFM. Other necessary elements for PFM to succeed include: ensuring active participation of the communities in the process; and, clarifying and harmonizing the rules and regulations at different levels